Entry into Training Programs and Its Effects on Training Outcomes: A Field Experiment - Hicks, William D.; Klimoski, Richard J. (Academy of Management Journal, 1987)
Most of the discussion and research on training has taken an organizational perspective. Assessing groups' needs for training, selecting appropriate training procedures, and determining how training should be evaluated have all figured as issues (Goldstein, 1974). Surprisingly little attention has been given to how the point of view of employees relates to expectations, attitudes, or decisions to select training programs. The type of announcement or prior information individuals receive about a training program and the amount of freedom they have to to take the program, two variables that could affect their entry into a training program, were the focus of this study.